OVERVIEW Overview of media-based education on zoss and first aid towards students’ knowledge at SDN 47 Jambi City: A Descriptive Study on the Effectiveness of Animated Educational Videos in Enhancing Safety Knowledge among Elementary School Students - Subandi, Andi; Noerjoedianto, Dwi; Taqwa, Muhammad (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Traffic accidents involving school-aged children are a public health concern in Indonesia, particularly due to inadequate road safety education. The School Safety Zone (Zona Selamat Sekolah/ZOSS) program and First Aid (P3K) knowledge are critical in reducing the impact of accidents, yet many students lack awareness. Educational innovations such as animated videos are considered more effective than traditional lectures in improving student knowledge. Method: This study used a one-group pretest-posttest design involving 30 students from SDN 47 Jambi City. The intervention consisted of an animated video covering ZOSS and First Aid materials, followed by discussion. Student knowledge was assessed using a validated questionnaire before and after the intervention. Data were analyzed using paired t-tests. Results: Prior to the intervention, 63.3% of students were in the